Legal mechanisms for the European Union to participate in the decision-making of multilateral fora in the field of maritime affairs - Hong, Wei-sheng (The University of Edinburgh, 2014)
The European Union (EU) increasingly participates in various arrangements at the international level in order to further the objectives of the Union. Yet, such participation poses challenges in terms of ensuring that the EU has an effective voice, whilst also ensuring certainty and clarity for other participants. This thesis focuses on the EU’s participation in the decision-making processes of multilateral fora in the field of maritime affairs in order to examine how these challenges can be met. The thesis explores the legal mechanisms in both EU law and international law that accommodate the ability of the EU to participate in international arrangements. It will consider whether these mechanisms ensure clarity and certainty to the key actors involved and whether consistency exists between the internal and external mechanisms. Through collecting, examining, and analysing historical and contemporary materials relating to the shaping and operating of the internal and external legal mechanisms, this thesis aims to explain and analyse how the legal mechanisms are established and how they can be adapted to meet the challenges facing the EU, its Member States, third States, and international institutions in a clearer and more consistent manner. The research diagnoses several key factors that have contributed to the possible ambiguity, uncertainty, and inconsistency of these mechanisms, including the evolving nature of shared competence and a heavy reliance on the Court of Justice in ascertaining and safeguarding the contours of the EU legal order and its interface with the international legal order. It then examines how the internal legal mechanisms have been projected externally, by using selected case studies of the participation of the EU in the International Maritime Organisation, the United Nations Convention on the Law of the Sea, the Food and Agriculture Organisation of the United Nations, and Regional Fisheries Management Organisations. This thesis illustrates that although various mechanisms have been adopted internally and externally to tackle the challenges facing the EU’s participation, several sets of asymmetries can be found across different legal mechanisms. The thesis evaluates the strengths and weaknesses of these mechanisms and it further suggests that adopting the mixed-participation mode for the EU and its Member States to participate in the multilateral fora may be preferable, or indeed necessary, even in areas where the EU enjoys an exclusive competence.
Keywords: international institution; external relations; European Union; competence; duty of co-operation; sui generis entity; mixed agreements